Endoscopic biliary stenting in a district general hospital. Issue 2 (August 1995) - Rao, K J; Varghese, N M; Blake, H; Theodossi, A
Abstract : During a 48 month period to December 1990, 367 patients, median age 75 years, with obstructive jaundice caused by common bile duct stones (201), malignant biliary obstruction (148), and benign biliary strictures (18), underwent therapeutic endoscopic retrograde cholangiopancreatography. Endoscopic biliary stenting and drainage was achieved in 343 of 367 patients attempted (93%), seven patients requiring a combined percutaneous endoscopic approach. Endoscopic stenting failed in 24 patients because of malignant duodenal infiltration (10), Billroth 2 gastrectomy (6), tight and extensive biliary strictures (6), peripapillary diverticulum (1), and technical failure (1). Prolonged follow up was available in 91% (311 of 343). The 30 day mortality was 5% (17 of 343), which included two procedure related deaths (0.6%) from fulminant pancreatitis and major sphincterotomy site bleeding. Early complications occurred in 14% (48 of 343) and late complications occurred in 11.9% (35 of 294) patients, as of the original 343, 17 had died within 30 days and another 32 were lost to follow up. Eighty patients with incomplete bile duct clearance and eight patients with benign biliary strictures had biliary stents inserted for 12-48 months (median 30). Endoscopic biliary stenting services are necessary in a district general hospital with technical success, death and morbidity rates comparable to other studies.